Empowerment As Replacement for the Three Laws of Robotics - Salge, Christoph; Polani, Daniel (Frontiers in Robotics and AI, 2017)
The greater ubiquity of robots creates a need for generic guidelines for robot behaviour. We focus less on how a robot can technically achieve a predefined goal, and more on what a robot should do in the first place. Particularly, we are interested in the question how a heuristic should look like which motivates the robot's behaviour in interaction with human agents. We make a concrete, operational proposal as to how the information-theoretic concept of empowerment can be used as a generic heuristic to quantify concepts such as self-preservation, protection of the human partner and responding to human actions. While elsewhere we studied involved single-agent scenarios in detail, here we present proof-of-principle scenarios demonstrating how empowerment interpreted in light of these perspectives allows one to specify core concepts with a similar aim as Asimov's Three Laws of Robotics in an operational way. Importantly, this route does not depend on having to establish an explicit verbalized understanding of human language and conventions in the robots. Also, it incorporates the ability to take into account a rich variety of different situations and types of robotic embodiment.